Identifying the historical significance of heritage houses in Davao City for conservation through adaptive reuse - Puntas, Sherwin O.; Orendain, Dan Jezreel A. (2017)
Heritage buildings give place their distinct character and at the same time offer a tangible connection to the past. Architecture has been an instrument to the display of cultural identity of a place. The construction of a building has a bigger role of depicting the history and culture and that of their settings are often ignored and honored as part of our cultural heritage. This research recommends a conservation method for heritage structures in Davao City through architectural documentation to preserve its cultural and historical value. Specifically, it aims to identify and classify features of architectural elements as tangible architectural heritage fabrics. The documentation of heritage structure features its architectural elements and highlights the houses? historical background. Furthermore, the evaluation of architectural elements defines the structure?s current physical condition in general. The research produced conservation guidelines for documented heritage structures according to its current physical conditions and suggested a potential utilization for the future development through conservation process.
Thesis (BS Architecture) -- University of the Philippines Mindanao, June 2017